"Information Technology; Law and Practice, Law & Emerging Technology Cyber Law & E-Commerce" - "Sharma, Vakul" (Gurgoan, 2016)
This book is not an internet download as most books of this genre are. It is an original work. It is more than a mere section wise commentary of the Information Technology Act, 2000. Numerous illustrations, concept notes and examples make the subject interesting and comprehensible.
Keywords: Law